2009
DOI: 10.1073/pnas.0807919106
|View full text |Cite
|
Sign up to set email alerts
|

ATP8B1 is essential for maintaining normal hearing

Abstract: ATP8B1 deficiency is caused by autosomal recessive mutations in ATP8B1, which encodes the putative phospatidylserine flippase ATP8B1 (formerly called FIC1). ATP8B1 deficiency is primarily characterized by cholestasis, but extrahepatic symptoms are also found. Because patients sometimes report reduced hearing capability, we investigated the role of ATP8B1 in auditory function. Here we show that ATP8B1/Atp8b1 deficiency, both in patients and in Atp8b1 G308V/G308V mutant mice, causes hearing loss, associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
103
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 48 publications
1
103
0
Order By: Relevance
“…21 In addition, they provide a striking parallel with the loss of stereocilia from the apical surface of the inner hair cells in Atp8b1 G308V/G308V mutant mice, which is associated with hearing loss. 9 Collectively, these data point to a general function of ATP8B1 in the formation or stabilization of microvillar structures. The perturbed ultrastructural morphology of the apical domain in ATP8B1-depleted Caco-2 cells is not caused by a general defect in apical protein sorting or stability, but is accompanied by a global change in its molecular composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In addition, they provide a striking parallel with the loss of stereocilia from the apical surface of the inner hair cells in Atp8b1 G308V/G308V mutant mice, which is associated with hearing loss. 9 Collectively, these data point to a general function of ATP8B1 in the formation or stabilization of microvillar structures. The perturbed ultrastructural morphology of the apical domain in ATP8B1-depleted Caco-2 cells is not caused by a general defect in apical protein sorting or stability, but is accompanied by a global change in its molecular composition.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The expression of ATP8B1 is not restricted to the canalicular membrane of hepatocytes 6,7 but extends to many different epithelial cell types. [7][8][9] This implies that, besides the role of ATP8B1 in bile salt secretion, the overall pathophysiology of ATP8B1 deficiency is the result of a more general cellular defect.…”
mentioning
confidence: 99%
“…Thus, they establish and maintain a physiologically essential asymmetry between the two leaflets, with phosphatidylserine (PS) and phosphatidylethanolamine (PE) being concentrated in the cytoplasmic leaflet and phosphatidylcholine (PC) and sphingomyelin in the exoplasmic leaflet. There are 14 human P4-ATPases, and mutations in many of these are linked to severe disorders (4)(5)(6)(7). On the basis of amino acid sequence alignment, the P4-ATPases are predicted to structurally resemble the classic P-type ATPase cation pumps Na + ,K + -ATPase and Ca 2+ -ATPase, possessing a transmembrane domain with 10 helices (M1-M10) and three cytoplasmic domains, P (phosphorylation), N (nucleotide binding), and A (actuator) (Fig.…”
mentioning
confidence: 99%
“…Biochemical studies have shown that P 4 -ATPases determine the curvature of the phospholipid bilayer by flipping aminophospholipids from the exoplasmic to the cytoplasmic leaflet. 29,30 ATPases have been implicated in human diseases such as ATP10C in Angelman syndrome, 31 ATP8B1 in hearing loss 32 and hereditary cholestasis, 33 and ATP8A2 in a severe neurological phenotype. 10 ATP8A2 is involved in the transport of aminophospholipids toward the cytoplasmic leaflet in brain cells, retinal photoreceptors and testis.…”
Section: We Identified Four Common Homozygous Regions In Two Affectedmentioning
confidence: 99%